Learning leadership development model of opportunity expansion school administration in the Northeast of Thailand - Thomson, Thunyamon; Wacharakul, Chiranan; Thawinkarn, Dawruwan; Ariratana, Wallapha (Edelweiss Applied Science and Technology, 2025)
This study aimed to (1) identify the components and indicators of learning leadership among school administrators in opportunity expansion schools in northeastern Thailand, (2) validate the consistency of these indicators with empirical data, (3) develop a corresponding learning leadership model, and (4) assess the model’s suitability, feasibility, and utility. In Phase 1, a comprehensive literature review and expert interviews established the key components and indicators. Phase 2 employed confirmatory factor analysis on data from 460 administrators and teachers—yielding χ² = 115.819, df = 97 (χ²/df = 1.194), p = 0.0935, RMSEA = 0.020, SRMR = 0.016, CFI = 0.997, and TLI = 0.996—to confirm model consistency. Phase 3 involved developing and evaluating a learning leadership model, which comprises a model name, principles and concepts, objectives, 28 practical guidelines, 13 success goals, and 23 mechanisms for driving success. Expert evaluations indicated that the model is highly suitable, feasible, and useful.